Al Mawaddah In The Quran (A Thematic Interpretation Perspective) - Darmawan, Agus; Mustofa, Ali; Mollah, Moch. Kalam (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This writing discusses the interpretation of al-mawaddah from the perspective of the Qur'an. The aim of this research is to understand how al-mawaddah is interpreted from the perspective of the Qur'an. To obtain data, the author conducted data collection through a literature study to understand the concepts of interpreting the term from the perspective of the Qur'an. From the data analysis conducted, the author found that al-mawaddah can be interpreted as "love expressed through attitudes and behaviors similar to obedience as a result of admiration for someone." The interpretation of the word mawaddah is not only associated with the context of marriage. However, after further research, it was found that the word mawaddah also speaks in the context of peace or friendship and even war. From the analysis of the verse on al-mawaddah, we can draw several important conclusions: compassion as the foundation of relationships, emotional involvement in relationships, mutual understanding and self-respect, relationships that understand and respect each party's uniqueness have the potential to develop well, compassion as an expression of love, emphasis on "signs for those who reflect" indicates that loving human relationships are one of the manifestations of Allah's greatness, and humans are invited to reflect and appreciate this blessing. The verse on al-mawaddah teaches that relationships based on love, mutual understanding, and compassion are not only desirable but also a religious mandate. This serves as a guideline for building a society characterized by love and tolerance, creating a peaceful and blessed environment. With this article, the author hopes to present a comprehensive understanding of the meaning of al-mawaddah